2015
DOI: 10.7461/jcen.2015.17.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of Surgical Site Closed Suction Drain for Pterional Craniotomy

Abstract: ObjectiveThe aim of this study was to assess the benefit of using a prophylactic surgical site closed suction drain in pterional craniotomy.Materials and MethodsA retrospective review was conducted on 607 consecutive patients who underwent a pterional craniotomy for treatment of intracranial anterior circulation aneurysms over a 5-year period. Between January 2000 and December 2004, 607 patients were divided into two groups, those who had a prophylactic suction drain during closure of the surgical site (drain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Wound healing is promoted, the dead cavity is eliminated. In contrast, other researchers [3][4][5][6][7][8] found that inserting a drainage tube during surgery did not significantly affect the incidence of complications at the surgical site. In neurosurgery, because the dura cannot be watertight sutured near the "parietal site", subgaleal fluid collection (SFC) often occurs.…”
Section: Introductionmentioning
confidence: 78%
“…Wound healing is promoted, the dead cavity is eliminated. In contrast, other researchers [3][4][5][6][7][8] found that inserting a drainage tube during surgery did not significantly affect the incidence of complications at the surgical site. In neurosurgery, because the dura cannot be watertight sutured near the "parietal site", subgaleal fluid collection (SFC) often occurs.…”
Section: Introductionmentioning
confidence: 78%
“…The placement of subgaleal drains with or without suction is often dependent on the experiences or preferences of the surgeons and/or intraoperative findings [11], the underlying hypothesis being the reduction subgaleal collection, thus avoiding wound tension, pain, and possibly (super) infection. However, previous studies suggest that the complication rate is not reduced after supratentorial craniotomies, but can include bradycardia [15,28,48], asystole [9,52], bleeding from the superior sagittal sinus [35], epidural hematomas [11,41,49], pseudohypoxic brain swelling with fatal courses [49], and The effect of drainage on recorded outcome parameters was analyzed using the binary logistic regression model. Outcome parameter at the time of discharge was decelerated as early follow-up; after 6 weeks, as late follow-up.…”
Section: Possible Complications and Side Effects After Placement Of Smentioning
confidence: 99%
“…Finally, the fascial incision and the scalp incision are closed in the usual manner. The choice of an extradural subgaleal closed suction drain should enhance the healing and reduce fluid collections under the flap [10].…”
Section: Closingmentioning
confidence: 99%